Neural algorithm for solving differential equations - Lee, Hyuk; Kang, In Seok (Journal of computational physics, 1990)
Finite difference equations are considered to solve differential equations numerically by utilizing minimization algorithms. Neural minimization algorithms for solving the finite difference equations are presented. Results of numerical simulation are described to demonstrate the method. Methods of implementing the algorithms are discussed. General features of the neural algorithms are discussed.